Optimal transmission power selecting algorithm for cluster based ultra-wide bandwidth wireless sensor networks - PAN Gao-feng; FENG Quan-yuan (Tongxin xuebao)
To solve the energy conservation and power control problem radically in the cluster based ultra wideband wireless sensor networks,an optimal transmission power selecting algorithm（OTPSA） was presented,the goal of which is,within the acceptable range of implementing cost,to get an optimal transmission power value based on the maximum transmission rate and the background noise level,as well as to achieve the required data transmission rate and to meet the energy conserving requirement to the greatest extent.The implementing feasibility,complexity and cost of the proposed algorithm have been analyzed and investigated in detail.The simulative results clearly show that the power consumed under OTPSA is greatly less than the maximum power gotten at each node,and can be regulated according to the fluctuation of the requirement of maximum rate and the background noise;sensor lifetime can also be prolonged by implementing the proposed scheme.Furthermore,the simulative results also indicate that the implementing cost of the presented algorithm is reasonable and acceptable.